Implementation of Coaching of Room Head on Work Motivation in Improving Caring Behavior of Implementing Nurses - Juliani Tarigan; Emiliana Tarigan; Sutanto Priyo Hastono (GLOBAL HEALTH SCIENCE GROUP, 2025)
Public demand for health services to provide quality services. Good quality is usually supported by high work motivation. Good work motivation provides humane care for patients. Humanist behavior treats patients as human beings who must be cared for and served with a sincere heart which is called Caring behavior. Caring behavior is an attitude of Caring and concern for patients. One of the efforts to improve the Caring behavior of nurses is through the implementation of coaching training provided by the head of the room and the head of the room provides coaching conversation sessions to implementing nurses. The purpose of the study was to find out the implementation of ward head coaching on work motivation and characteristics of implementing nurses in increasing Caring behavior at M. Tangerang Hospital. This research method uses a quantitative method with a quasi-experimental design with a pretest-post-test control group design, namely a two-group design that was selected by consecutive sampling. The samples of this study by consecutive sampling, were 40 nurses 30 nurses in the intervention group and 10 nurses in the control group. The head coaching technique training with pre and post test scores got an increase of 24%. Univariate results showed an increase in Caring behavior in the intervention group by 10% after the implementation of coaching. The results of the independent sample t-test obtained a significance value (Sig.) of 0.029, smaller than 0.05, indicating that there was a difference in Caring behavior between the nurses in the intervention group and the nurses in the control group after the implementation of coaching by the head of the room. Suggestions for further research are to conduct research using qualitative methods.